THE GENUS TETRACERA (DILLENIACEAE) IN THE EASTERN OLD WORLD - HOOGLAND, R. D. (Research Center for Biology, 1953)
1. An account of the genus Tetracera L. in the eastern Old World (Asia, Malaysia,Australia, New Caledonia) is given. The Malaysian species have already been in cluded in the revision of the Dilleniaceae in